Bumpy rides: School to work transitions in South Africa - Todd Pugatch (Institute for the Study of Labor (IZA), 2012)
Re-enrollment in school following a period of dropout is a common feature of the South African school to work transition that has been largely ignored in both the literature on South Africa and the wider literature on sequential schooling choice. In this paper, I quantify the importance of the option to re-enroll in the school to work transition of South African youth. I estimate a structural model of schooling choice in South Africa using a panel dataset that contains the entire schooling and labor market histories of sampled youth. Estimates of the model's structural parameters confirm the hypothesis that enrollment choices reflect dynamic updating of the relative returns to schooling versus labor market participation. In a policy simulation under which re-enrollment prior to high school completion is completely restricted, the proportion completing at least 12 years of schooling rises 6 percentage points, as youth who would have dropped out under unrestricted re-enrollment reconsider the long-term consequences of doing so. The results suggest that the option to re-enroll is an important component of the incentives South African youth face when making schooling decisions.
urn:nbn:de:101:1-201204239642
Keywords: I21; J24; O12; 330; human capital investment; labor supply; youth unemployment; dynamic discrete choice; South Africa; Berufseinstieg; Jugendarbeitslosigkeit; Schulbesuch; Südafrika